An Overview on Indian Knowledge System - Khan, Salim; Sharma, Meeta (Integrated Journal for Research in Arts and Humanities, 2024)
The Indian knowledge system (IKS) seeks to actively support, and advance research aimed at addressing contemporary societal challenges. Rooted in the rich tradition of Vedic literature, including the Vedas and the Upanishads, IKS is poised for integration into digital learning platforms. To enhance the quality of classroom instruction on IKS courses, tailored modules for educator training and orientation are under consideration. Specialized teacher training centers will be established, focusing on specific topics within the Indian Knowledge Systems. Innovation within IKS will be fostered through initiatives like Grand National Challenges, National Competitions, and Hackathons, with incentives provided for groundbreaking ideas. Collaboration with global institutions, facilitated by entities like the Indian Council of Historical Research (ICHR), will enable the conduct of India-centric research. To catalyze the founding of Indian knowledge System in numerous Higher Education Institutions (HEIs), initial seed financing will be provided. Outreach efforts targeting the public will employ diverse mechanisms to spread and promote genuine IKS. Public involvement will be encouraged via Jan Bhagidari programs, akin to citizen science initiatives. Youth will find job prospects through skill-based programs, and IKS will actively foster tradition knowledge by leveraging technological keys to platform Indian inheritance globally. The overarching goal is to capture 10% of world tourism, thereby generating substantial employment opportunities for the youth.